LOCAL GOVERNMENT INNITIATIVE ON EDUCATION SECTOR - Diana Rochintaniawati; Ella Wargadinata (Institut Pemerintahan Dalam Negeri (IPDN), 2018)
The Study of Educational Policy post decentralization related on Professional Development was conducted in three years research. There are two problems posed in the study, they are: what kind of policy that should be provided by the local government to support the improvement of teacher professional development in teaching science of elementary school teachers and what type of teacher training model that should be developed to enhance teacher professional development in teaching science in elementary school. The subject of the study involved 30 elementary school teachers from West Bandung and Cimahi District as well as district Educational government as a policy maker. Research and Development method was apply in the study. The first year study started from elementary school teachers’ needs analysis in teaching science as basic information which was used to develop a framework of teacher training model. In the second year, the model of teacher training was developed and tested in small scale trial involving 3 schools and large scale trial involving 15 schools. The policies that should be provided by the local government to support the continuity of the program were also identified in a second year of research. In the third year of the study, the model was disseminated involving elementary schools located in West Bandung and Cimahi. From the study it was reveal that the involvement of local government policy post decentralization can support effectiveness of teacher training program as more schools were get involved in the training program as well as it maintain the continuity of the program. The teacher training model that mixed between traditional model and lesson study model was proved as an effective model to enhance elementary school teachers’ professional development in teaching science which was supported by the local government policy.